Journal of Gambling Studies - Grant, Jon E.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Journal of Gambling Studies is an interdisciplinary forum for the dissemination on the many aspects of gambling behavior, both controlled and pathological, as well as variety of problems attendant to, or resultant from, gambling behavior including alcoholism, suicide, crime, and a number of other mental health problems. Articles published in this journal are representative of a cross-section of disciplines including psychiatry, psychology, sociology, political science, criminology, and social work.
Keywords: Psychiatry; Economics; Management science; Sociology; Community psychology; Environmental psychology; Psychiatry; Sociology, general; Community and Environmental Psychology; Economics, general